2021
DOI: 10.1016/j.semcancer.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the heritable risk of breast cancer: From statistical methods to susceptibility genes

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…Genome-wide estimates were compared with LD score regression (LDsc) results (28). Gold-standard methods require raw data; however, previous studies have shown that LDsc has comparable performance in most scenarios (22). Since LDsc is routinely used to estimate heritability for the traits in the UK BioBank, we retrieved the results for all 38 cancers and compared them to BAGHERA estimates.…”
Section: Comparison With State-of-the-art Methods For Genome-wide and Local Heritability Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome-wide estimates were compared with LD score regression (LDsc) results (28). Gold-standard methods require raw data; however, previous studies have shown that LDsc has comparable performance in most scenarios (22). Since LDsc is routinely used to estimate heritability for the traits in the UK BioBank, we retrieved the results for all 38 cancers and compared them to BAGHERA estimates.…”
Section: Comparison With State-of-the-art Methods For Genome-wide and Local Heritability Estimationmentioning
confidence: 99%
“…Heritability analysis provides the statistical framework to estimate the contribution of all common SNPs to cancer risk regardless of their statistical significance and effect size (16). Studying heritability is now becoming a crucial step in cancer GWAS and has provided insights on the risk of developing many malignancies (17), including prostate (18), cervical (19), testicular germ cell tumor (20) and breast cancer (21,22). However, since the functional impact of the SNPs is context-dependent (23), it is important to quantify the amount of heritability explained by genomic regions associated with well-characterized biological functions (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…SNP refers to the polymorphism of the DNA sequence caused by the variation of a single nucleotide at the genomic level. SNPs are widely found in the human genome and can influence the expression and function of key genes involved in tumorigenesis 11–13 . A study in HNSCC found that SNPs of ADH are associated with tumorigenesis, possibly due to their key role in regulating acetaldehyde formation 14 .…”
Section: Discussionmentioning
confidence: 99%
“…However, these treatments burden patients with side effects that reduce therapy compliance and quality of life. In most patients where BC arises not from single gene mutations (or discrete combinations) [5,6], selective estrogen-receptor modulators (SERMs), e.g., tamoxifen and raloxifene, are approved for both the treatment and prevention of BC and decrease BC risk by about 35% [7]. However, tamoxifen is rarely used in clinics for prevention due to serious side effects such as endometrial cancer [8,9].…”
Section: Introductionmentioning
confidence: 99%